An Analysis of Slang Word in Used on Titled “All The Small Things” and “What My Age Again” in Song Lyrics by Blink 182 - Dzaqi Ahmad Ramdani; Riandi Riandi; Tatu Munawaroh (Journal of English Education Studies, 2026)
The use of slang words among teenagers is currently very widespread so that almost all teenagers use slang words in everyday life and on social media Facebook. The use of slang words can make it difficult for the other person to understand, especially for people who are not used to slang. This study uses a qualitative descriptive method with a data collection technique in the form of a lyric on titled “All the Small Things” and “What My Age Again” on Enema of the State Album (1999). The data collection technique was carried out by listening lyric on Youtube and Spotify. These slang words have as explained by the following experts Allan and Burridge (in Manurung et all, 2020) theory to divide slang words affirm that there are five types into Fresh and Creative, Flippant, Imitative, Acronym, Clipping and taken from Community Inggris Fabelia (2022), namely offensive slang, vulgar slang, and taboo slang.the results of the data analysis that the researcher successfully total 13 (thirteen) obtained slang word on lyric “All the Small Things” and “What My Age Agains”, there were at least 3 (three) slang words in the Fresh and Creative type (prank phone calls, cops, roses), 2 (two) slang words in the clipping type (ain’t, you’ll), 2 (two) slang words i- the acronym type (ADD, ID), 4 (four) slang words in the offensive slang type (Nobody likes you when you're twenty-three, My friends say I should act my age, And you still act like you're in freshman year, Work sucks, I know), and 2 (two) slang words in the vulgar slang type (sodomy, and she took off my pants). For the Flippant slang type, which is imitation slang, the researcher did not find any data. Therefore, to get criticism and also give other students the opportunity to find other slang words, both in the same song and in different songs. In addition, slang can also be used to convey messages more concisely, create group identity, or even as a form of humor in songs.